Investigating The Impacts Of English Podcasts On Students Listening Skills - Syamsul Bahri; Shally Ashriani Zahra; Lukmanul Hakim (Journal of Islamic Multidiciplinary Research, 2026)
English podcasts are digital audio media that provide authentic exposure to the English language and support the development of listening skills. This study aimed to investigate students’ perceptions on English podcasts, the benefits gained, and the expectations regarding podcast use in listening learning. A descriptive qualitative approach was employed, with data collected through semi-structured interviews involving ten students from the English Education Department of UIN Ar-Raniry Banda Aceh who had experience using podcasts in listening activities. The findings revealed that students generally held positive perceptions on English podcasts, describing them as interesting, enjoyable, and effective learning media. The reported benefits included improved pronunciation awareness, better listening comprehension, expanded vocabulary, increased motivation for independent learning, and greater familiarity with various English accents used in international communication. Students also expected podcasts to be integrated more frequently into listening classes with materials suited to their proficiency levels. These findings suggest that podcasts are valuable tools for enhancing listening instruction and learning outcomes